Impact of HPV status on immune responses in head and neck squamous cell carcinoma. (April 2022) - Qureshi, Hannan A.; Zhu, Xiaodong; Yang, Grace H.; Steadele, Melissa; Pierce, Robert H.; Futran, Neal D.; Lee, Sylvia M.; Méndez, Eduardo; Houghton, A. McGarry
Highlights: Expanded TIL populations display activity against autologous tumor. HPV + HNSCC harbors an enhanced B cell signature as compared to HPV- HNSCC. Combined B cell and plasma cell signature predicts favorable response to ICI. Abstract: The main objective of our study was to understand the impact of immune cell composition and the tumor-reactivity of tumor infiltrating lymphocytes (TIL) in HPV-positive (HPV + ) and HPV-negative (HPV - ) head and neck squamous cell carcinoma (HNSCC). TIL cultures were established from primary HNSCC tumors, the T cell subsets were phenotypically characterized using flow cytometry, and Interferon (IFN)-γ ELISA assay was used to determine TIL function. NanoString Immune Profiler was used to determine an immune signature by HPV-status, and multiplex immunohistochemistry (MIHC) was used to quantify immune cell distributions and their spatial relationships. Results showed that HPV + and HPV - HNSCC had similar capacity to expand IFN-γ reactive TIL populations, and these TIL populations had similar characteristics. NanoString analysis revealed increased differential expression of genes related to B cell functions in HPV + HNSCC, which were significant at a Benjamini-Yekutieli adjusted p -value of < 0.001. MIHC also displayed increased CD8 + T cell and CD19/CD20 + B cell densities in the tumor region of HPV + HNSCC as opposed to HPV - HNSCC ( p < 0.01). Increases in a combined metric of tumor B cell content and stromal plasma cell content was associated with increased progression-free survival in HPV - HNSCC patients treated with immune checkpoint inhibitor therapy ( p = 0.03). In summary, TIL populations expanded from HPV + and HPV - HNSCC displayed similar IFN-γ reactivity. However, we identified a strong B-cell signature present within HPV + HNSCC, and higher B and plasma cell content associated with improved PFS in HPV - HNSCC patients treated with immune checkpoint inhibitors.